Signing on for dirty work: Taking stock of a public psychiatry project from the inside. (August 2016) - Pope, Leah G.; Cubellis, Lauren; Hopper, Kim
As applied anthropologists used to working at arm's length from public psychiatry, we step out of the daily grind to take stock of the challenges of taking on ethnography entrained–harnessed to the implementation of a new program. These include the loss of critical distance, the struggles to negotiate locally viable forms of authority and relevance, the necessity of sustaining a Janus-faced relation with principal players, the urgency of seeing time-sensitive information converted into corrective feedback, and the undeniable attraction of being part of "committed work" with game-changing potential. In so doing, we rework the terms of witnessing and revive an old alternative: that documentary dirty work be reclaimed as a variant of public anthropology, one that transforms the work of application from mere afterthought to integral part of the original inquiry.